Impact of morphine use on mortality in STEMI patients treated with primary PCI - preliminary data from a new registry. (11th May 2021) - Szabo, D; Szabo, A; Edes, IF; Becker, D; Merkely, B; Hizoh, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Background Opioids decrease the effect of P2Y12 receptor inhibitors in vitro and observational reports suggest that morphine use is associated with larger infarct size. Our research group presented previously, using a prospective single-center registry, that periprocedural morphine use may have no impact on long-term mortality in STEMI patients treated with primary PCI and clopidogrel. Purpose Our purpose is to check this interaction using a new registry of patients treated according to the current guidelines, including novel antiplatelet agents. Methods From May until November 2020, we collected 196 STEMI patients treated with primary PCI. 88 (44.9%) of them got morphine during the prehospital and periprocedural care. Baseline demographic, anamnestic, procedural, and laboratory data were collected. Survival data were analysed using Kaplan-Meier survival curves and the log-rank test. To adjust for confounding, a 1:1 propensity score-matching analysis was performed using 114 cases. Results An adequate balance on baseline covariates was achieved during propensity score-matching. Kaplan-Meier analysis showed no difference in 30-days mortality of the patients treated with or without morphine neither in the original nor in the propensity score-matched population (p = 0.094 and p = 0.309, respectively). Conclusion: Our preliminary data suggest that morphine may have no impact on mortality in STEMI patients treated with primary PCI and medical therapy according to the current guidelines including novel P2Y12 antagonists.